Placebo Effect in Obsessive-Compulsive Disorder (OCD). Placebo Response and Placebo Responders in OCD: The Trend Over Time - Kotzalidis, Georgios D.; Del Casale, Antonio; Simmaco, Maurizio; Pancheri, Lucia; Brugnoli, Roberto; Paolini, Marco; Gualtieri, Ida; Ferracuti, Stefano; Savoja, Valeria; Cuomo, Ilaria; De Chiara, Lavinia; Mosca, Alessio; et al. (Current Neuropharmacology, 2019)
Background: Placebo response appears to be increasing in antidepressant, antipsychotic and various internal medicine trials. A similar trend has been reported for OCD during 1989-1999. Placebo response is generally considered as the extent to which placebo treatment is associated with core symptom improvement. In this analysis, we used Joinpoint regression to assess the time trend of both placebo response and placebo responder rates according to the year of publication with no time restriction in OCD drug trials. Methods: We included drug and/or psychotherapy trials vs. placebo from PubMed, Embase, CINAHL, and PsycINFO retrieved through the search (placebo OR sham) AND (obsessive* OR OCD). We included studies through investigator consensus. We then performed on data of included studies log-linear joinpoint segmented regression models using a p<0.05 cutoff. Results: We included 113 studies from 112 published papers. Placebo mean annual response rates in OCD studies significantly increased from 1991 to 2017 with an annual percent change (APC) of 0.66%, while placebo mean annual responder rates also significantly increased from 2010 to 2017, with an APC of 5.45%. Drug mean annual response rates in OCD studies significantly increased from 1987 to 2012 with an APC of 0.72%, while the corresponding responder rates did not show statistically significant APC changes between 1984 and 2017. Conclusion: We observed a tendency for placebo to increase both measures of response in OCD clinical drug trials through the years that tend to approximate the responses shown by drugs. Changes in the type of study (moving from classical head to head comparisons to add-on studies in treatmentresistant populations) and countries involved in experimentation may partially account for some portion of these results. It appears that placebo effects are becoming more elusive and out of control.
Keywords: placebo effect